PIGR predicts good clinical outcomes and plays a tumor suppressor role in the development of breast cancer - Jiang, Tengfei; Sun, Zhi; Dong, Ke; Pu, Qian; Gao, Haidong; Lv, Yanrong; Li, Peng; Zhao, Guanghui (Frontiers in Oncology, 2025)
IntroductionBreast cancer (BRCA) is a phenotypically and functionally heterogeneous disease. New biomarkers or therapeutic targets must be discovered to improve treatment effects. The polymeric immunoglobulin receptor (PIGR) plays an anti-cancer role in various human malignancies. This study aimed to explore the prognostic significance and possible function of PIGR in BRCA.MethodsData from TCGA and GEO, and methods such as logistic regression analysis, Kaplan-Meier survival analysis, multivariate Cox analysis, GO, KEGG, and GSEA were employed to detect the effects of PIGR on BRCA bioinformatically. RT-qPCR, Western blot analysis, and immunohistochemistry were used to validate the expression of PIGR in BRCA. The effects of PIGR on BRCA were also detected in vitro and in vivo.ResultsThe expression level of PIGR was down-regulated in BRCA tissues. CCK-8 proliferation and colony formation assay demonstrated that overexpression of PIGR could inhibit breast cancer cell proliferation, clone formation, and migration. In vivo experiments confirmed these results. GSEA revealed that PIGR differentially expressed genes are mainly associated with the immune response. The expression level of PIGR significantly correlated with the infiltration of immune cells and the abundance of immune-related molecules.ConclusionsPIGR can suppress breast cancer cell growth in vitro and in vivo and is an independent protective factor for BRCA patients’ prognosis. PIGR correlates with tumor immunity and exerts anti-tumor effects in BRCA. PIGR might be a novel prognostic biomarker and therapeutic target.